Protein domains governing interactions between E2F, the retinoblastoma gene product, and human papillomavirus type 16 E7 protein. - Huang, P S (1993)
Human papillomaviruses (HPVs) are the etiological agents for genital warts and contribute to the development of cervical cancer in humans. The HPV E7 gene product is expressed in these diseases, and the E7 genes from HPV types 16 and 18 contribute to transformation in mammalian cells. Mutation and deletion analysis of this gene suggests that the transforming activity of the protein product resides in the same domain as that which is directly involved in complex formation with the retinoblastoma gene product (pRB). This domain is one of two conserved regions (designated CRI and CRII) shared by E7 and other viral oncoproteins which bind pRB, including adenovirus E1A protein. Binding of HPV type 16 E7 protein to pRB has previously been shown to affect pRB's ability to bind DNA and to form complexes with other cellular proteins. In the current study, we map the functional interaction between E7 protein and pRB by monitoring the association between a 60-kDa version of the pRB, pRB60, and the cellular transcription factor E2F. We observe that CRII of E7 (amino acids 20 to 29), which completely blocks binding of full-length E7 protein, is necessary but not sufficient to inhibit E2F/pRB60 complex formation. While CRI of E1A (amino acids 37 to 55) appears to be sufficient to compete with E2F for binding to pRB60, the equivalent region of E7 is neither necessary nor sufficient. Only E7 fragments that contained both CRII and at least a portion of the zinc-binding domain (amino acids 60 to 98) inhibited E2F/pRB60 complex formation. These results suggest that pRB60 associates with E7 and E2F through overlapping but distinct domains.